The Council of psychological advisers. [article]. - Sunstein, Cass R.
Findings in behavioral science, including psychology, have influenced policies and reforms in many nations. Choice architecture can affect outcomes even if material incentives are not involved. In some contexts, default rules, simplication, and social norms have had even larger effects that significant economic incentives. Psychological research is helping to inform initiatives in savings, finance, highway safety, consumer protection, crime, corruption, health, and the environment. No nation has yet created a council of psychological advisers, but the role of behavior research in policy domains is likely to grow in the coming years, especially in light of the mounting interests in promoting ease and simplication ("navigability"); in increasing effectiveness, economic growth, and competitiveness; and in providing low-cost, choice-preserving approaches. -- (from the author)
Keywords: Behavioral economics; Nudge; Default rules; Social norms